The Sanctuary of Artemis Soteira in the Kerameikos of Athens - Graml, Constanze (Philippika Altertumskundliche Abhandlungen, 2020)
Cover -- Title Pages -- Contents -- Foreword -- Preliminaries -- 1 Introduction -- 1.1 The So-Called Hekateion - a Detective Story About the History of Research and Its Consequences -- 1.1.1 Discovery and First Excavation of the Sanctuary by Kyriakos Mylonas in 1890 -- 1.1.2 Excavation Campaigns from 1907 to 1915 by Alfred Brueckner and the Sondage of Camillo Praschniker and Konstantinos Rhomaios in 1910 -- 1.1.3 The First Restoration Works Carried Out by Alfred Brueckner and Hubert Knackfuß in 1914/1915 -- 1.1.4 Post-Second-World-War Restoration Carried Out by Dieter Ohly -- 1.1.5 Work Conducted During the Era of Franz Willemsen (1961-1975) -- 1.1.6 Work Conducted During the Directorship of Ursula Knigge (1975-1995) -- 1.1.7 The Cleaning Campaigns in 2012 and 2013 and the Following Restoration Work Under the Auspices of Jutta Stroszeck -- 1.1.8 The Excavation Campaign 2015 Under the Directorship of Jutta Stroszeck - a Sanctuary Within the Sanctuary -- 1.1.9 History of Research on the temenos and Certain Finds With Provenance in the Sanctuary -- 1.2 Approaching What Is Already Known? Methodology of the Investigation At Hand -- 2 Back to the Beginning: Reconstructing the Archaeological Evidence at the Time of the Discovery -- 2.1 The Enclosing Walls -- 2.2 Built Structures Used for Ritual Practice -- 2.2.1 The Rectangular Block-Shaped Altar and the Adjacent Table -- 2.2.2 The Basis With the Prismatic Recess -- 2.2.3 The Omphaloid Monument and Its Substructure -- 2.3 Further Built Structures Within the temenos -- 2.3.1 Well B 18 and Its Phases of Use -- 2.3.2 The Cylindrical Lime Stone Block: a Possible Sundial -- 3 Finds From the temenos Area and Their Critical Evaluation -- 3.1 Potential Biases of the Small Finds -- 3.2 Analysis of the Finds - Chronology, Original Provenance of the Artefacts, and Function in the Sanctuary.